Development and content validation of the Burden of Documentation for Nurses and Midwives (BurDoNsaM) survey - Brown, Janie; Cooper, Alannah; Albrecht, Matthew (WILEY, 2020)
Aim: To develop a validated tool to measure nursing and midwifery documentation burden. Background: While an important record of care, documentation can be burdensome for nurses and midwives and may remove them from direct patient care, resulting in decreased job satisfaction, associated with decreased patient satisfaction. The amount of documentation is increasing at a time where staff rationalisation results in decreasing numbers of clinicians at the bedside. No instrument is available to measure staff perceptions of the burden of clinical documentation.